2005
DOI: 10.1029/2005gl024267
|View full text |Cite
|
Sign up to set email alerts
|

Observational evidence of sensitivity of surface climate changes to land types and urbanization

Abstract: [1] Sensitivity of surface climate change to land types is investigated for the Northern Hemisphere by subtracting the reanalysis from the observed surface temperature (OMR). The basis of this approach is that while reanalysis represents the large-scale climate changes due to greenhouse gases and atmospheric circulation, it is less sensitive to regional surface processes associated with land types. OMR trends derived from two independent reanalyses (ERA40 and NNR) and two observations (CRU and GHCN) show simil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
102
3
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(122 citation statements)
references
References 24 publications
16
102
3
1
Order By: Relevance
“…Interestingly, the oil palm and rubber plantations were only slightly warmer than the forests whereas the young oil palm plantations had clearly higher LST than the other vegetated surfaces. For other parts of the world, Lim et al (2005Lim et al ( , 2008, Fall et al (2010) and Weng et al (2004) also observed cooler temperatures for forests and the highest surface temperatures for barren and urban areas. In Indonesia, land transformation is often not instantaneous from forest to oil palm or rubber plantation but can be associated with several years of bare or abandoned land in-between (Sheil et al, 2009).…”
Section: Lst Patterns Across Different Land Use and Land Cover (Lulc)mentioning
confidence: 99%
“…Interestingly, the oil palm and rubber plantations were only slightly warmer than the forests whereas the young oil palm plantations had clearly higher LST than the other vegetated surfaces. For other parts of the world, Lim et al (2005Lim et al ( , 2008, Fall et al (2010) and Weng et al (2004) also observed cooler temperatures for forests and the highest surface temperatures for barren and urban areas. In Indonesia, land transformation is often not instantaneous from forest to oil palm or rubber plantation but can be associated with several years of bare or abandoned land in-between (Sheil et al, 2009).…”
Section: Lst Patterns Across Different Land Use and Land Cover (Lulc)mentioning
confidence: 99%
“…The OMR method is based on the fact that the reanalysis data did not assimilate observed surface information. This method does provide some signatures consistent with the distribution of underlying surface properties [22,[29][30][31][32][33][34][35][36]. However, whether or not the OMR fully represents the impact of LUCC is still controversial [37,38].…”
mentioning
confidence: 99%
“…In recent years urban boundary layer research has received more attention, as people have realized that urbanization has impacts on weather and climate (Changnon, 1992;Martilli, 2002;Kalnay and Cai, 2003;Shepherd and Burian, 2003;Lim et al, 2005;Best, 2006). Studies on the urban boundary layer have been carried out through various approaches including observational experiment, physical modelling and numerical simulation.…”
Section: Introductionmentioning
confidence: 99%